Assessment of emergency gathering points and temporary shelter areas for disaster resilience in Elazığ, Turkey - SİYAVUŞ, AHMET EMRAH (My University, 2023)
Cities are profoundly vulnerable to the impacts of disasters due to their densely populated nature. Consequently, strategies are being formulated to optimize resource utilization within urban areas and their immediate surroundings. Resilient cities constitute a key facet of these strategies, capable of adapting to and enduring the pressures arising from social, economic, and environmental adversities. The establishment of resilient cities often involves the identification of emergency gathering and shelter sites to mitigate the potential aftermath of disasters and emergencies. In Turkey, such sites are designated by the Provincial Directorates under the aegis of the Disaster and Emergency Management Presidency (AFAD). These designations are guided by specific criteria. The present study focused on the suitability and selection of 95 emergency gathering points and 4 temporary shelter locations in Elâzığ, situated within Turkey’s East Anatolian Fault Zone. For this analysis, the ArcGIS Pro software (ESRI 2021) was employed to assess the distribution, area sizes, and accessibility of open and green spaces earmarked as emergency gathering points across the city. Additionally, the Service Area Analysis was leveraged to delineate the utility of these sites during and following disaster scenarios. The findings of the analysis unveiled several noteworthy insights. It was evident that in Elâzığ, a city with a population of 381,153, meeting areas were deficient in terms of both quantity and size across 38 neighborhoods. Furthermore, almost half of the designated assembly points fell short in terms of optimal location and accessibility. Moreover, the study revealed inadequacies in the number, capacity, and accessibility of disaster shelter locations. These revelations underline the imperative for more comprehensive and effective planning to bolster the resilience of cities in the face of potential disasters.
Keywords: Tarımsal Bilimler; Ziraat; Toprak ve Bitki Besleme; Toprak ve Su Muhafazası ve Amenajmanı; Havza Yönetimi; Atmosfer Bilimleri ve Meteoroloji Mühendisliği; Jeofizik Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Soil and Plant Feed; Soil and Water Storage and Management; Watershed Management; Atmospheric Sciences and Meteorological Engineering; Geophysical Engineering; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Temel Bilimler (SCI); Çevre / Ekoloji; Yerbilimleri; SU KAYNAKLARI; JEOKİMYA VE JEOFİZİK; METEOROLOJİ VE ATMOSFER BİLİMLERİ; Agriculture & Environment Sciences (AGE); Natural Sciences (SCI); ENVIRONMENT/ECOLOGY; GEOSCIENCES; WATER RESOURCES; GEOCHEMISTRY & GEOPHYSICS; METEOROLOGY & ATMOSPHERIC SCIENCES; Su Bilimi ve Teknolojisi; Fizik Bilimleri; Atmosfer Bilimi; Dünya ve Gezegen Bilimleri (çeşitli); Water Science and Technology; Physical Sciences; Atmospheric Science; Earth and Planetary Sciences (miscellaneous); Disaster risk reduction; Emergency assembly point; Temporary shelter area